2006
DOI: 10.1074/jbc.m510622200
|View full text |Cite
|
Sign up to set email alerts
|

Compensatory Increase in Hepatic Lipogenesis in Mice with Conditional Intestine-specific Mttp Deficiency

Abstract: Microsomal TG transfer protein (MTTP) is required for the assembly and secretion of TG (TG)-rich lipoproteins from both enterocytes and hepatocytes. Liver-specific deletion of Mttp produced a dramatic reduction in plasma very low density lipoprotein-TG and virtually eliminated apolipoprotein B100 (apoB100) secretion yet caused only modest reductions in plasma apoB48 and apoB48 secretion from primary hepatocytes. These observations prompted us to examine the phenotype following intestine-specific Mttp deletion … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
114
1

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 112 publications
(132 citation statements)
references
References 33 publications
17
114
1
Order By: Relevance
“…However, although FFA accumulation has not been observed in the liver-specific MTP knock-out mice (6, 36), intestine-specific MTP ablation has been reported to increase cellular free fatty acids (7). We also observed an ϳ1.5-fold increase in intestinal free fatty acids (Table 1).…”
Section: Mtp and Abca1 Gene Ablations Reduce Cholesterol Secretion Bysupporting
confidence: 62%
See 3 more Smart Citations
“…However, although FFA accumulation has not been observed in the liver-specific MTP knock-out mice (6, 36), intestine-specific MTP ablation has been reported to increase cellular free fatty acids (7). We also observed an ϳ1.5-fold increase in intestinal free fatty acids (Table 1).…”
Section: Mtp and Abca1 Gene Ablations Reduce Cholesterol Secretion Bysupporting
confidence: 62%
“…However, Xie et al (7) reported that I-Mttp Ϫ/Ϫ decreased fractional cholesterol absorption by ϳ60 -70%. This discrepancy is the result of two different methods used to measure cholesterol absorption.…”
Section: Role Of Intestinal Mtp and Abca1 In Lipid Absorption-mentioning
confidence: 99%
See 2 more Smart Citations
“…This protein plays a crucial role in chylomicron synthesis. Indeed, an intestine-specific MTP gene invalidation produces a dramatic decrease in chylomicron synthesis and secretion (5). Finally, the induction of apoA-IV expression found in lipid-fed mice might also facilitate intestinal lipoprotein production (27).…”
Section: Discussionmentioning
confidence: 99%